Cabaran Digital, Penyelesaian al-Quran: Kajian Tematik tentang Keibubapaan dalam al-Quran - Abror, Mhd. Abror, M.Ag; Nadya Nela Rosa; Lina Eka Retnaningsih; Abrillia Jasandra (Advances in Humanities and Contemporary Studies, 2025)
The rapid advancement of technology today presents new challenges across various aspects of life, particularly in children's education. The ease of access to information through the internet and social media has made children more vulnerable to negative content that can erode their moral and ethical values. In this context, the implementation of appropriate parenting strategies becomes a crucial key in shaping children's character in accordance with noble values. This study aims to examine the relevance of Islamic parenting, as outlined in the Qur'an, in addressing the contemporary challenges faced by Muslim families in the digital era. The research employs a library-based approach using thematic interpretation (maudhū‘i) to explore Qur’anic verses related to child-rearing. The findings reveal that Islamic parenting principles—such as role modeling, the instillation of monotheism (tawḥīd), effective communication, social supervision, and compassion—are highly relevant to modern parenting needs. While the forms and methods of parenting may evolve with the times, the fundamental Qur’anic values must remain the foundation in raising children amid the challenges of the digital age.